The Relationship of Perceived Value, Perceived Risk, and Level of Trust Towards Green Products of Fast Moving Consumer Goods Purchase Intention - Rizka Zulfikar; Prihatini Ade Mayvita (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2018)
This study aims to investigate how the relation between the perceived value, perceived risk, level of trust and toward green products purchase intention. This study is a survey research using questionnaires as an instrument. Population and sample used in this study is the community of Banjarmasin and taken as many as 150 respondents using non-purposive sampling method. The study found that Banjarmasin’s public tends to be more considered in its functional value indicators than other indicators such as social value, emotional value, and economic value. They also tend to be more considered at time risk indicators than other indicators such as the risk of physical and psychological risks. Banjarmasin’s public tends to be more considered toward its benefits indicators than other indicators such as trust in the object, and trust in attributes. Perceived value and perceived risk affect the level of public confidence but have no effect to the public purchase intention towards green products. The level of trust significantly influences the purchase intention towards green products. The relationship between the public purchase intention towards green products with the perceived value and perceived risk tends to be indirect and moderated by variable levels of trust.